What is XLIFF and why should I use it? a brief overview of the XML localization interchange file format (XLIFF). - Jewtushenko, Tony (SOA webservices journal.)
Much time, energy and commitment are required to develop and self successful software products and Web based services. Most products of this type are initially developed for a specific language and locale (e.g. U.S. English). To maximize return on investment, products can be customized so they may be available to the largest possible market-the global market. This customization process is known as localization.